Differences in dynamic functional connectivity between musicians and non-musicians during naturalistic music listening - Dai, Ruijiao; Toiviainen, Petri; Campo, Fulvia Francesca; Brattico, Elvira (Frontiers in Neuroscience, 2025)
IntroductionBased on tens of neuroimaging studies and a meta-analysis, we know that music expertise is associated with increases in brain volume and activity in structures related to audition, action, and various cognitive functions. What is less known is how music expertise affects the brain’s functional connectivity during music listening.MethodsA novel algorithm, Leading Eigenvector Dynamic Analysis, was used to extract the specific dynamic patterns and the corresponding transition process during a naturalistic free-listening paradigm between 18 musicians and 18 non-musicians.ResultsWe found a brain state involving the frontal, orbitofrontal, parietal, and anterior cingulate cortex, associated with higher cognitive functions, emotional regulation, and reward, to be more recurrent in musicians during music listening compared to non-musicians. Transition processes revealed heightened engagement in areas linked to auditory processing, somatosensory integration, cognitive function, and emotional regulation in musicians. This enhanced dynamic connectivity might be linked to musicians’ ability to integrate complex auditory stimuli and derive emotional meaning from them. Non-musicians, conversely, showed a tendency to engage more with the default mode network during music listening, possibly in relation to self-relevant mental processes and connection with personal experiences while being absorbed with the music.DiscussionThese findings highlight how music expertise shapes functional connectivity dynamics, musicians enhancing sensorimotor-cognitive integration and non-musicians relying on emotion and personal engagement.